2005
DOI: 10.1074/jbc.m502698200
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model for the Membrane-bound Form of the Juxtamembrane Domain of the Epidermal Growth Factor Receptor

Abstract: The epidermal growth factor receptor (EGFR) is a member of the receptor tyrosine kinase family involved in the regulation of cellular proliferation and differentiation. Its juxtamembrane domain (JX), the region located between the transmembrane and kinase domains, plays important roles in receptor trafficking. Two sorting signals, a PXXP motif and a 658 LL 659 motif, are responsible for basolateral sorting in polarized epithelial cells, and a 679 LL 680 motif targets the ligand-activated receptor for lysosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 67 publications
6
35
0
Order By: Relevance
“…In agreement with the crystal structure, the region just before Gly672 (i.e., Glu661-Gly672), which is negatively charged and contains a central PxxP sequence, is unstructured (48). Our results appear to disagree with the solution NMR studies: the N-terminal JM helix (residues 652-661) observed in their studies overlaps the unstructured JM sequence in our TM-JM peptides.…”
Section: Discussionsupporting
confidence: 71%
“…In agreement with the crystal structure, the region just before Gly672 (i.e., Glu661-Gly672), which is negatively charged and contains a central PxxP sequence, is unstructured (48). Our results appear to disagree with the solution NMR studies: the N-terminal JM helix (residues 652-661) observed in their studies overlaps the unstructured JM sequence in our TM-JM peptides.…”
Section: Discussionsupporting
confidence: 71%
“…Molecular dynamics simulations suggest that when EGFR is in an inactive conformation, the LRRLL motif within the JM-A segment is buried in the membrane (Arkhipov et al), consistent with NMR data for the isolated juxtamembrane segment of EGFR in detergent micelles (Choowongkomon et al, 2005). These observations suggest that the nature of the interaction between the transmembrane helices toggles the configuration and membrane association of the JM-A portion of the juxtamembrane segments (Figure 7A).…”
Section: Discussionsupporting
confidence: 70%
“…Upon N-terminal TMD dimerization, the JM-A segments interact with the membrane and form an α-helical, antiparallel homo-dimer (8,39,40). The α-helical structure of the JM-A dimer has been confirmed in NMR and MD simulation studies of TMD-JM-A fragments (2,8,41) and in MD simulation of the active EGFR dimer (8).…”
Section: Resultsmentioning
confidence: 70%